Year book of agricultural co-operation 1972 - McCready, K.J. (Oxford : Basil Blackwell, 1972)
This second Year Book during Co-operative Development decades has taken as its major theme the state of co-operation in the Middle East: an area where two distinct types of co-operation exist.
The Plunkett foundation for co-operative studies.
Includes bibliographic references and index.
rpm 23/01/2019
Loans
Keywords: Agriculture, Cooperative; Agriculture, Cooperative; Agriculture, Cooperative